The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12302-020-00347-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 31 endocrine-disrupting compounds in the Taihu Lake and application of the fish plasma model

Abstract: Background: The successful application of Fish plasma model (FPM) will greatly simplify the risk assessment of drugs. At present, the FPM has been applied to the risk assessment of several human drugs with high hydrophobicity. However, its applicability to a wide variety of compounds needs to be tested. Field work about distribution characteristics of endocrine disrupting compounds (EDCs) in water and in fish plasma plays a key role in promoting the successful application of FPM. However, there are few reports… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 52 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Only a handful of studies have investigated the distribution of pharmaceuticals within the bodies of exposed wild fish , where drug accumulation is compound- and species-specific. , Instead, the majority of distribution data available for pharmaceuticals in fish are from time-course laboratory bioconcentration studies. In one such study, atenolol and venlafaxine displayed tissue-specific distribution in zebrafish, with bioaccumulation directly correlating with the lipid content of each tissue .…”
Section: Susceptibility Of Fish To Human Apis In the Environment – In...mentioning
confidence: 99%
“…Only a handful of studies have investigated the distribution of pharmaceuticals within the bodies of exposed wild fish , where drug accumulation is compound- and species-specific. , Instead, the majority of distribution data available for pharmaceuticals in fish are from time-course laboratory bioconcentration studies. In one such study, atenolol and venlafaxine displayed tissue-specific distribution in zebrafish, with bioaccumulation directly correlating with the lipid content of each tissue .…”
Section: Susceptibility Of Fish To Human Apis In the Environment – In...mentioning
confidence: 99%
“…In short, the reliability of FPC prediction by the FPM for polar drugs and certain fish species needs further verification. Our previous work 16 on 31 polar endocrine disrupting compounds (EDCs) in the plasma of wild fish from Lake Taihu showed that the bioaccumulation of EDCs in fish plasma is not only dependent on hydrophobicity but also fish species-specific and compound-dependent. The classic FPM was appropriate for only a few EDCs (7 of 20), and the FPM underestimated the log BAFs (bioaccumulation factors) of the most less hydrophobic EDCs (log Kow : 1.5–3.5, 11 out of 20) while overestimating the log BAFs of several relatively higher hydrophobic EDCs (log Kow : 3.87–5.9) in fish plasma.…”
Section: Introductionmentioning
confidence: 99%